Infinitely many solutions for nonlocal elliptic systems of (p1(x), ⋯, pn(x))‐Kirchhoff type. (4th November 2015) - Miao, Qing
Abstract : In this paper, we obtain the existence of infinitely solutions for a class of nonlocal elliptic systems of ( p 1 ( x ), ⋯, p n ( x ))‐Kirchhoff type. Our main results are new. Our approach are based on general variational principle because of B. Ricceri and the theory of the variable exponent Sobolev spaces. Copyright © 2015 John Wiley & Sons, Ltd.